SUBSTANSI BUDAYA DALAM KEBIJAKAN TATARUANG DI BALI - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2010)
This article analyses essential elements of Balineseculture, which are formulative of land use planningfor Bali.Using ethnographic and hermeneutic methodologies and a cultural matrix derived from E.T.Hall(1973),strategic territorialitiesare defined and correlated to ninedimensions of culture. The study is contextualised by the ongoing debate over the challenges Balifaces in conserving its cultural heritage while achievingits development objectives. The results emerge from Fundamental Research Scheme funded by the IndonesianDepartment for Education.